Plan de negocios de un autolavado de vehículos en la Localidad de Suba. (2023)
Entrepreneurship colloquially is a way to achieve economic independence, especially in times of crisis, or is it what most people perceive and that it has become very popular to be able to start a business and succeed in the process, but this really goes beyond, because a venture is a business initiative that is started by one person, directs it and is in charge of making all the effort work, developing ideas and improving processes throughout the project.